Rights for Development. An analysis of the strengths and weaknesses of human rights approach to overcoming food insecurity and gender discrimination - Camacho Mejía, Guisela (2021)
This article explores the advantages and disadvantages of using a human rights-based approach to addressing two persistent development challenges: food insecurity and gender discrimination. As an exploratory paper, it does not propose a thesis but rather defines key concepts and legal norms of the human rights-based approach (HRBA), as well as its implications for food security and gender discrimination. Despite its exploratory nature, the paper remains a fair starting point for a more critical examination of the role played by human rights in the development field. This paper is divided into four sections. The first section lays forth a theoretical framework for HRBA, emphasizing its key features and operational principles. The second section explores the benefits and drawbacks of using HRBA to achieve development goals. The third section proposes some guidelines to achieve a world without hunger and food insecurity. The fourth section discusses how HRBA might contribute to overcoming gender discrimination. Finally, I outline the main takeaways.